Anti-Neuroinflammatory Effects of Prenylated Indole Alkaloids from the Antarctic Fungus Aspergillus sp. Strain SF-7367 - Zhiming Liu; Chi-Su Yoon; Thao Quyen Cao; Hwan Lee; Il-Chan Kim; Joung Han Yim; Jae Hak Sohn; Dong-Sung Lee; Hyuncheol Oh (Molecules)
Inflammation has always been considered a trigger or consequence of neurodegenerative diseases, and the inhibition of inflammation in the central nervous system can effectively protect nerve cells. Several studies have indicated that various natural products inhibit neuroinflammation. Among these, Antarctic fungal metabolites have pharmacological activities and a developmental value. Therefore, this study aimed to evaluate the anti-neuroinflammatory activity of an Antarctic fungus belonging to Aspergillus (strain SF-7367). Secondary metabolites of SF-7367 were isolated using high-performance liquid chromatography followed by validation of their anti-inflammatory effects in lipopolysaccharide-stimulated BV2 microglia and RAW264.7 macrophages. Chemical analysis of metabolites from the fungal strain revealed five known compounds: epideoxybrevianamide E (1), brevianamide V/W (2), brevianamide K (3), brevianamide Q (4), and brevianamide R (5). Among these compounds, brevianamide K showed significant anti-inflammatory activity against both cell types. Results of Western blotting and molecular docking showed that brevianamide K could regulate the activation of nuclear factor kappa-light-chain-enhancer of activated B cell (NF-κB) signaling. This indicates that brevianamide K present in Aspergillus sp. (strain SF-7367) can inhibit inflammatory responses by reducing lipopolysaccharide-induced nuclear translocation of NF-κB (p65). These findings suggest that Aspergillus sp. (strain SF-7367) and brevianamide K are candidate agents for treating neurodegenerative diseases.